Performance Outcomes In Learning Additional Mathematics By Grey Theory Approach - Abu Bakar Hasan; Norizarina Ishak; Sharma Rao A/l Balakrishnan (Medwell Publications, 2024)
Grey system theory has evolved, since, it was first introduced roughly 40years ago. It has been used in many applications and environments by different researchers worldwide. The aim of this study is to demonstrate the said theory in education environment by looking at the performance outcome in learning a mathematical subject at secondary school level through analysis and forecasting. The results show that the GM(1,1) Model produced 3.8% mean relative percentage error and future research will focus on how to optimize the forecasting.